Research into specifics of recycling the scale of nickelmolybdenum containing precision alloys by the method of hydrogen reduction - Hryhoriev, Stanislav; Petryshchev, Artem; Kovalyov, Andriy; Shyshkanova, Ganna; Yamshinskij, Mykhail; Fedorov, Grigoriy; Chumachenko, Yaroslav; Mizerna, Olena; Goliev, Yevgen; Shcherbyna, Oksana (Eastern-European Journal of Enterprise Technologies, 2017)
We explored kinetic patterns of hydrogen reduction of the scale of a nickelmolybdenum containing precision alloy at a temperature of 673‒1573 K over the interval from 0 to 360 min. The largest degree of reduction is achieved after thermal treatment at 1273 K – 99 %. This is due to the intensification of reduction processes and a sufficient level of porosity, which enables a satisfactory gas exchange. It was discovered that the starting scale consists mainly of Fe2O3 and Fe3O4 with the atoms substituting their alloying elements, as well as MoO3. The target product of metallization had a sponge microstructure and consisted of γFe, FeNi, the phase of Mo, and the remaining nonreduced Fe3O4 and FeO. The resulting phases do not demonstrate a noticeable inclination to sublimation. This ensures a reduction in the losses of alloying elements when obtaining and using the highlyalloyed metallized scale, which was confirmed by the experimental industrial tests. At the same time, disposal of industrial wastes provides a reduction in the technogenic load on industrial regions and improves ecological situation.